Immunosuppressants and/or antivascular endothelial growth factor inhibitors in punctate inner choroidopathy? Follow-up results with optical coherence tomography angiography. Issue 8 (18th October 2018) - Pohlmann, Dominika; Pleyer, Uwe; Joussen, Antonia M; Winterhalter, Sibylle
Abstract : Purpose: To report the effectiveness of treatment with antivascular endothelial growth factor (VEGF)-inhibitor and/or immunosuppressants in punctate inner choroidopathy (PIC) using standard imaging modalities and optical coherence tomography angiography (OCTA) over a time period of 16 months. Methods: In this prospective, unmasked, single-centre study, 23 individuals with PIC underwent imaging with spectral domain OCT, fluorescein angiography, indocyanine green angiography and OCTA. Two groups were formed based on systemic treatment. In case of choroidal neovascularisation (CNV) activity, intravitreal anti-VEGF injections were carried out in both groups. Results: Group I included 12 patients (24 eyes) with 18 affected eyes (75%) who did not receive any systemic therapy at baseline. Group II contained 11 patients (22 eyes) who started systemic immunosuppressive therapy on average 2 years before baseline. All eyes with recurrence of CNV or residual fluid (group I: seven eyes; group II: six eyes) received anti-VEGF agents. Group I showed a significant reduction of CNV size (p=0.0078), as well as a decrease of fluid retention (p=0.0078) on OCTA after anti-VEGF injection. Group II did not demonstrate any significant reduction of CNV size, vessel shape or fluid retention post injection. But overall, fluid accumulation was significantly lower in group II (median=0.03 mm 2 ) than in group I (median=0.32 mm 2 ) (p=0.0028). Conclusion: Immunosuppressants in addition to anti-VEGF agents showed a significant reduction of fluid accumulation, that is, reduced disease activity. We conclude that there is a benefit and effectiveness of immunosuppressants to control inflammatory secondary CNV in PIC.